Effects of six different preventive treatments on the shear bond strength of orthodontic brackets: in vitro study - Gianguido Cossellu; Valentina Lanteri; Andrea Butera; Michele Sarcina; Giampietro Farronato (Medical Journals Sweden, 2015)
Objective: The aim of this study is to evaluate the effect of six different prophylactic agents on shear bond strength (SBS) of orthodontic brackets. Materials and methods: One hundred twenty-six freshly extracted mandibular bovine incisors were used. Teeth were randomly divided into 7 equal groups (18 per group) as follows: group-1 served as control with no pre-treatment; group-2 enamel treated with fluoride varnish (Fluor Protector, Ivoclar Vivadent); group-3 containing casein-phosphopeptide-amorphous calcium-phosphate (CPP-ACP) paste (GC Tooth Mousse, RECALDENT™); group-4 with ozone (HealOzone, Kavo); group-5 with glycine powder (Perio Flow, EMS); group-6 with hydroxyapatite powder 99.5% (Coswell S.p.A.); group-7 with a toothpaste made of hydroxyapatite nanocrystals (BioRepair® Plus, Coswell S.p.A). Brackets were all bonded using the same technique with transbond XT (3 M Unitek, Monrovia, CA). All the bonded specimens were stored for 24 h in deionized water (37 °C) and subjected to thermal cycling for 1000 cycles. The SBS was measured with an Instron Universal Testing machine and the adhesive remnant was assessed with the adhesive remnant index (ARI) using a stereomicroscope at 10× magnification. Results: Statistical differences (ANOVA) were found among the seven investigated groups (F = 12.226, p < 0.001). SBS of groups 2, 5 and 6 were significantly lower than the control group (p < 0.05). ARI scores (chi-square test) were correlated with the differences of SBS values. Conclusion: CPP-ACP paste, ozone or BioRepair® did not compromise on bracket bond strength. Fluoride, glycine or hydroxyapatite significantly decreased the SBS; only the fluoride group showed significant clinically low (<6 MPa) SBS values.